Application of LoRa Technology at Distribution Substation Using Peak Load Data - Purnama Helena Hutabarat; Mhd Fitra Zambak (Faculty of Engineering, Universitas Tanjungpura, 2022)
The process of monitoring and measuring transformers at PT. PLN (Persero) at the distribution substation BR 391 is done manually during peak load hours in the field, usually between 18.00-22.00 local time. Distribution substations sometimes have different peak load hours, in the morning, afternoon, evening, and sometimes during the day. Taking into account the different peak load hours at different substations, the current peak load hours are still determined by human. It is not effective, to overcome this, in this study it is planned to design a monitor and data storage using LoRa technology to monitor transformers at distribution substations all the time and has been tested at distribution substation BR 391 Jl. Wijaya Kusuma Medan. From the observations, peak load hours occur between 18.00-22.00 WIB and the highest peak load with power per phase: R=20,513,40 watts, S=15,350.06 watts, and T=21,323.91 watts. It can be seen that the highest average daily power consumption is at 20.00 WIB. More load usage occurs at night and the highest load is in the T phase. The increase in load affects the temperature increase of the cable up to 42.6℃